Social capital, policy fairness, and subjective life satisfaction of earthquake survivors in Wenchuan, China: a longitudinal study based on post-earthquake survey data - Wang, Dianxi; Li, Danyang (Health and quality of life outcomes, 2020)
Existing research has rarely examined an earthquake's sustained impact and the trajectory of the earthquake survivors' life satisfaction over time. This study aims to analyze longitudinal changes in life satisfaction of Wenchuan earthquake survivors and the impact of social capital and government relief policy. This research applied a hierarchical linear model to longitudinal survey data collected after the earthquake. The survey was divided into three waves and was collected from Deyang City and Mianyang City of Sichuan Province. A random sampling method was used; a sample of 225 participants had valid responses over three waves of the survey. This study found that a survivor's social capital and the perception of the fairness of government relief policy have a significant effect on the trajectory of life satisfaction post-disaster. First, the initial life satisfaction of those with high social capital was significantly higher than of those with low social capital, whilst survivors with high social capital had a lower rate of change in life satisfaction. Second, one year after the earthquake, those who felt government policy was unfair had a lower life satisfaction than those who felt it was fair. However, from the first year to the fourth year after the disaster, survivors who believed that the government policy was unfair experienced a higher rate of change in life satisfaction than those who did not. Third, the fairness of government relief policy moderates the relationship between survivors' social capital and changes in life satisfaction. A fair policy of relief can reduce the negative impact of the lack of individual social capital on life satisfaction. Survivors reconstruct life satisfaction through their social network and the perception of the fairness of the government's post-disaster relief policy. Therefore, to promote the improvement of life satisfaction of survivors, it is necessary to cultivate social capital and ensure fairness of the relief policy.